A point mutation in the EGF-4 domain of β3 integrin is responsible for the formation of the Seca platelet alloantigen and affects receptor function - Sachs, Ulrich J.; Bakchoul, Tamam; Eva, Olga; Giptner, Astrid; Bein, Gregor; Aster, Richard H.; Gitter, Maria; Peterson, Julie; Santoso, Sentot (Thrombosis and Haemostasis, 2012)
Neonatal alloimmune thrombocytopenia (NAIT) is caused by fetomaternal platelet incompatibility with maternal antibodies crossing the placenta and destroying fetal platelets. Antibodies against human platelet antigen-1a (HPA-1a) and HPA-5b are responsible for the majority of NAIT cases. We observed a suspected NAIT in a newborn with a platelet count of 25 G/l and petechial haemorrhages. Serological analysis of maternal serum revealed an immunisation against αIIbβ3 on paternal platelets only, indicating the presence of an antibody against a new rare alloantigen (Seca) residing on αIIbβ3. The location of Seca on αIIbβ3 was confirmed by immunoprecipitation. Nucleotide sequence analysis of paternal β3 revealed a single nucleotide exchange (G1818T) in exon 11 of the β3 gene (ITGB3), changing Lys580 (wild-type) to Asn580 (Seca). Two additional members of the family Sec were typed Seca positive, but none of 300 blood donors. Chinese hamster ovary cells expressing Asn580, but not Lys580 αIIbβ3, bound anti-Seca, which was corroborated by immunoprecipitation. Adhesion of transfected cells onto immobilised fibrinogen showed reduced binding of the Asn580 variant compared to wild-type αIIbβ3. Analysis of transfected cells with anti-LIBS and PAC-1 antibody showed reduced binding when compared to the wild-type. No such effects were observed with Seca positive platelets, which, however, are heterozygous for the Lys580Asn mutation. In this study, we describe a NAIT case caused by maternal alloimmunisation against a new antigen on αIIbβ3. Analysis with mutant transfected cells showed that the Lys580Asn mutation responsible for the formation of the Seca antigenic determinant affects αIIbβ3 receptor function.
Keywords: NAIT; HPA; thrombocytopenia; GP IIb/IIIa